FAST Observation of Polarized Radio Emission of Rotating Radio Transient J2325−0530 - Shi-jun Dang; Zi-wei Wu; Ji-guang Lu; Peng Jiang; Wei Li; Yu-lan Liu; Yan-qing Cai; Jian-ping Yuan; Na Wang (The Astrophysical Journal, 2025)
In this study, we present a detailed analysis of single-pulse emission from the rotating radio transient (RRAT) J2325−0530, observed at 1250 MHz using the Five-hundred-meter Aperture Spherical Radio Telescope. A total of 168 burst pulses were detected within 0.8 hr of observation, yielding a detection rate 3 to 4 times higher than those previously reported. For the first time in this RRAT, we detected sequences of consecutive single-pulse emission lasting two to six spin periods. The single pulses exhibit significant variability in linear polarization, circular polarization, and polarization position angle, while the average profile displays weak polarization and a complex position angle structure. The distributions of fluence and waiting time, together with the significant correlation between fluence and pulse width, indicate that the emission behavior of RRAT J2325−0530 resembles that of giant pulse phenomena. We also measured the scintillation bandwidth and timescale at 1250 MHz to be 3.45 ± 0.07 MHz and 16.67 ± 0.35 minutes, respectively. In three single pulses, we detected quasiperiodic microstructure in the Stokes I , L , and V parameters, with differing microstructure periods across these components. Nevertheless, the observed microstructure periods follow the known linear relationship with the pulsar rotation period. These results support the view that RRATs share the same underlying emission physics of normal pulsars, while also revealing additional complexity in the origin of microstructure.